2010
DOI: 10.1021/ie100637b
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic-Operational Mechanism to Autothermal Reforming of Methane

Abstract: A reforming experiment was performed using a nickel catalyst, with the goal of suggesting a mechanism for the autothermal reforming of methane (ATR), under thermally neutral conditions. To bring the process to future scale-up at a fixed-bed reactor, kinetic-operational evaluations were made while taking into account the parameters of the gas phase flow and the temperature. From these evaluations, based on conversions, yields, and selectivities, it was possible to develop a novel approach to a descriptive mathe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…The authors suggested that the proposed kinetic model can be apply in industry to design the process conditions and evaluation of the effect of the inlet gas composition to syngas production including the elimination of the deactivation process and coke deposition on catalytic surface. Souza et al [114] studied the mechanism of the autothermal reforming of methane over nickel based catalysts (ATR). They reported about the high rates of methane conversions at lower temperature compared to the methane reforming processes and that synthesis gas is produced via two steps which includes total oxidation of methane followed by steam reforming of methane and dry reforming of methane.…”
Section: Oxy-steam Reforming Of the Methane Reaction Mechanismmentioning
confidence: 99%
“…The authors suggested that the proposed kinetic model can be apply in industry to design the process conditions and evaluation of the effect of the inlet gas composition to syngas production including the elimination of the deactivation process and coke deposition on catalytic surface. Souza et al [114] studied the mechanism of the autothermal reforming of methane over nickel based catalysts (ATR). They reported about the high rates of methane conversions at lower temperature compared to the methane reforming processes and that synthesis gas is produced via two steps which includes total oxidation of methane followed by steam reforming of methane and dry reforming of methane.…”
Section: Oxy-steam Reforming Of the Methane Reaction Mechanismmentioning
confidence: 99%
“…As illustrated in previous studies for Ni‐based catalysts at similar conditions, methane, CO 2 and intermediates adsorb and react on the same type of active site. The reversibility of methane adsorption and dissociation is supported by the influence of H 2 addition to the feed gas. The methane dissociation generates adsorbed carbon and associated hydrogen atom, which is supposed to be at thermodynamic equilibrium. The adsorption and dissociation of carbon dioxide are considered as reversible (Eq. ) by using 13 CO isotopic tracer techniques .…”
Section: Resultsmentioning
confidence: 99%
“…The reversibility of methane adsorption and dissociation is supported by the influence of H 2 addition to the feed gas. The methane dissociation generates adsorbed carbon and associated hydrogen atom, 31,32 which is supposed to be at thermodynamic equilibrium.…”
Section: Carbon Depositionmentioning
confidence: 99%
“…The Gibbs reactor is equal to a 0 D thermodynamic equilibrium calculation based on the Gibbs free energy minimization including not only ideal gases but also condensed species such as solid carbon [50]. The validity of this assumption is shown in several previously published studies [16,47,51]. It should be mentioned here that high gas hourly space velocities (GHSV) can lead to a gas composition at the reformer outlet, which is not close to the chemical equilibrium.…”
Section: Reformer Modellingmentioning
confidence: 99%